VOCABULARY LEARNING STRATEGIES USED BY MALE AND FEMALE LEARNERS OF HIGHER INTERMEDIATE LEVEL - Arina Afiyati Shadikah (Jurnal Pendidikan, Sains Sosial, dan Agama, 2020)
Abstract This recent study focuses on the use of vocabulary learning strategies (VLSs). Nevertheless, in this study the subject was categorized based on gender (male and female). This study aims to identify vocabulary learning strategies employed by female and male learner in learning new vocabularies. The method of this study is qualitative. The participants are 10 male learners and 10 female learners of higher intermediate level at LBPP LIA Solo. The data were collected using vocabulary learning strategy questionnaires (VLSQs), interview, documentations, and test. The data collected were analyzed qualitatively. The research finding showed that female learners tend to use more vocabulary learning strategies than male did. In addition, the most vocabulary learning strategies used by female learners were dictionary strategies and memory strategy: rehearsal as the least vocabulary learning strategies used. Meanwhile, male learners indicated to use guessing strategies more often and note-taking strategy rarely. Keywords : VLSs, Higher Intermediate Level, Male Learners, Female Learners.